Trending over thinking – quick fame, quiet genius: the bad habits of social media - Raluca Iuliana GEORGESCU; Dumitru Alexandru BODISLAV; Ionuț Valeriu ANDREI (Theoretical and Applied Economics, 2025)

(untitled)
This article explores the cultural and psychological shift in how societies attribute value in the digital era, emphasizing the increasing preference for visibility and immediate recognition over substantive, long-term achievement. Drawing from interdisciplinary fields such as neuroeconomics, behavioural psychology, sociology, and media theory, the study investigates how cognitive biases – such as effort discounting, temporal discounting, and availability heuristics – interact with dopamine-driven reward systems to shape perception in an attention-based economy. The authors argue that social media and platform capitalism have transformed prestige into performative visibility, undermining civic virtue, intellectual effort, and institutional trust. By integrating insights from evolutionary psychology and cultural anthropology, the article provides a theoretical framework for understanding this transition and its implications for education, democracy, and individual well-being. It concludes with policy and pedagogical recommendations aimed at revaluing effort, mastery, and ethical contribution in a digitally saturated society.